Development and Test of a Short Message on Manual Materials Handling Hazards and Controls in Small and Micro Businesses. Issue 1 (2nd January 2018) - Yazdani, Amin; Ngo, Binh; Schwenk, Grace; Sawicki, Ben; Bigelow, Phil; Callaghan, Jack; Carlan, Niki; Lambraki, Irene; Wells, Richard
Abstract : OCCUPATIONAL APPLICATIONS Small and micro businesses generally face challenges during occupational health and safety processes such as hazard identification and control, often more so for hazards related to musculoskeletal disorders. 'Store it off the Floor', a message based on mitigating a major risk factor for development of low back pain, was well received by owners and managers in 40 small businesses. Conceptual and instrumental knowledge utilization was demonstrated following the distribution of a dual-purpose poster/toolbox talk handout containing the noted message. Such an approach has the potential to reduce a major hazard for developing or aggravating low back pain in large numbers of workers. This dissemination method may also be applicable to reduce other risk factors for musculoskeletal disorders and improve working conditions. TECHNICAL ABSTRACT Background : To reduce the substantial burden of low back pain, there is a need to identify workplace hazards, evaluate them, prioritize tasks for intervention, and develop and implement appropriate controls. Small and micro businesses often face challenges during hazard identification and control processes, particularly for hazards related to Musculoskeletal Disorders (MSD). Purpose : To determine the efficacy of a simple message ('Store it off the Floor') to facilitate knowledge increase, which is the first step towards mitigating a major risk factor for development of low back pain. Methods : Surveys along with probing questions were employed in a cross-sectional qualitative study design with a single follow-up time point. Knowledge utilization was evaluated following distribution of a dual-purpose toolbox talk handout/poster in 40 small businesses. Results : The message was well received by the small business owners and managers, and conceptual and instrumental knowledge utilization was demonstrated. Overall, 37% of participants indicated that they were already aware of the issue, while 63% responded that after reviewing the poster, their method of thinking about lifting changed. A substantial proportion of participants (32%) spoke to somebody about potential changes. A subset (28%) of businesses described some form of use, while six businesses (15%) stated that they had already made changes. Conclusions : This approach has the potential to increase knowledge and its utilization about a major lifting hazard and the selection of controls other than lift training. The dissemination method used here may also be applicable to reduce other risk factors for musculoskeletal disorders and improve working conditions.